Crack nucleation and propagation in rounded cohesive granular media - I. Preechawuttipong (2018)
This work investigates the influence of cohesion on aspects of fracture mode and propagation in 2D rounded cohesive granular packing. Simulations are undertaken using the molecular dynamics method involving simple contact laws with adhesion. The numerical "Brazilian" test with samples of 8000 circular particles suggests that the formation of crystallized agglomerates within mono-disperse samples depends on the value of the cohesive energy between particles. The agglomerate size is increased when the surface energy increases. In the testing phase and for high values of surface energy, the fissures appear at the agglomerate interfaces in the center of sample and propagate toward the periphery in parallel to the compressive direction. © 2006 - IOS Press and the authors. All rights reserved.